STRATEGI PENERAPAN COLLABORATIVE GOVERNANCE DALAM PROGRAM PEDESTRIAN JALAN HOS COKROAMINOTO KABUPATEN PONOROGO - Anugerah Wibowo, Putra; Khoirurrosyidin; Triono, Bambang (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2023)
This study aims to determine the model and process of collaborative governance in the face off program Jalan Hos Cokroaminoto Ponorogo. The approach used in this study is a qualitative approach. Qualitative research is research that produces descriptive data in the form of written or spoken words from people and observed behavior. The results of this study are based on the analysis and field observations that have been carried out, collaborative governance in the face off program at Jalan Hos Cokroaminoto Ponorogo. The collaborative governance model that is applied in the face off of the Hos Cokroaminoto street is carried out with all stakeholders of the organization, shops, banks, and the community itself to make pedestrians in the Hos Cokroaminoto area work together with all parties. The function of this collaboration is so that the local community of the area can prepare themselves for the changes caused by an increase in tourists in Ponorogo Regency, especially in the Face Off Hos Cokroaminoto area and can provide satisfying services for visitors.